Effects of corn steep liquor supplementation on intake and digestion of tallgrass prairie hay contaminated with sericea lespedeza - Eckerle, G.J.; Pacheco, L.A.; Olson, K. C.; Jaeger, John R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Sericea lespedeza (Lespedeza cuneata) is a noxious weed that infests approximately 600,000 acres of native range in Kansas. Intake of sericea lespedeza by grazing beef cattle is poor due to the presence of condensed tannins in the plant. Condensed tannins reduce protein digestion by beef cattle and may also decrease plant palatability because of their astringent nature. Prolific seed production, in combination with little or no grazing pressure, has contributed to the rapid spread of sericea lespedeza in the Flint Hills. Increasing grazing pressure on sericea lespedeza may reduce seed production and slow its advance; however, the presence of condensed tannins inhibit consumption by grazing animals. Reports have indicated that feed-grade polyethylene glycol may inhibit formation of tannin-protein complexes in the rumen, but beef producers have not widely adopted polyethylene glycol because, at the rates necessary to increase intake of sericea lespedeza, it is cost-prohibitive and disallowed by regulations. Therefore, identifying substances that are generally regarded as safe (GRAS) by the U.S. Food and Drug Administration, cost-effective, and that mitigate the consequences of consuming a diet high in tannins is advantageous. Such information could lead to a degree of biological control of this noxious weed using the most economically important grazer (i.e., beef cattle) in the Flint Hills. Preliminary research in our laboratory indicated that corn steep liquor has binding affinity for condensed tannins that is similar to polyethylene glycol. Therefore, the objective of our study was to determine the effects of corn steep liquor supplementation on intake and digestion of tallgrass prairie hay contaminated by sericea lespedeza.
Keywords: Beef; Corn steep liquor; Intake; Digestion; Sericea lespedeza